Lysosomal signaling in control of degradation pathways. (April 2016) - Huber, Lukas A; Teis, David
Abstract : Autophagy mediates the (non-)selective bulk degradation of cytoplasm, protein aggregates, damaged organelles and certain pathogens. The endosomal membrane system uses multivesicular bodies (MVBs) to selectively deliver ubiquitinated membrane proteins together with extracellular components into lysosomes. Microautophagy (MA) and chaperone-mediated autophagy (CMA) additionally contribute to the selective delivery of cargo into lysosomes. The coordinated function of these lysosomal degradation pathways is essential to maintain cellular homeostasis. Their activity is controlled by mTOR (mammalian target of rapamycin) signaling and thus coupled to metabolic processes during cell growth. Here, we will discuss how TORC1 on lysosomes and TORC2 at the plasma membrane coordinate the different membrane biogenesis pathways with cargo selection, vesicle transport and fusion with lysosomes in response to intracellular and extracellular cues.